Spatiotemporal variation of tintinnid microzooplankton (Ciliophora: tintinnina) from Sarawak inshore water, South China Sea - Kumar, Uttam; Mustafa Kamal, Abu Hena; Karim, Nurul Ulfah; Wan Rasdi, Nadiah; Das, Jewel; Idris, Mohd Hanafi; Abualreesh, Muyassar H.; Ismail, Johan (Springer, 2021)
Unraveling planktonic community patterns and their linkage with the surrounding ecology is essential for aquatic resource management. Studies on the tintinnid microzooplankton in most of the marine waters of Malaysian South China Sea (SCS) are scarce though the trophic role of this community is well established. Thus, we aimed to investigate on spatiotemporal pattern of composition, abundance, and biomass of tintinnid, and how this community patterns are regulated with the basic ecological parameters. A total of 46 species were recorded, mostly in southwest monsoon (33 species) during the study period from May 2016 to April 2017. Tintinnopsis was counted as major genera with 19 species, and Tintinnopsis radix, a species that reported as neritic-estuarine origin calculated as the most abundant (11%) in our study. Both the space and time were equally responsible for differences in species richness, diversity, abundance, and biomass. However, species richness variation was not influenced by space–time interaction, whereas we observed season (time) and species size worked as a strong factor in terms of biomass variations. Accordingly, the higher mean abundance (Station 3; 132,116 ind m−3 in southwest monsoon) did not scale up to the bigger mean biomass (Station 4; 1.317 µgC L−1 in Inter-monsoon April). Among the ecological variables, the strongest influence was observed in the tintinnid community by pH, dissolved oxygen and salinity mostly during southwest monsoon around Bintulu-Mukah areas. Similarly, species-specific affinity to pH was also observed by most of the species. In addition, Favella campanula showed affinity to salinity, turbidity, and conductivity, while T. cylindrica and T. gracilis were driven by the temperature and dissolved oxygen. The findings of this research may help to explore comprehensive food web dynamics in future ecosystem studies in SCS region.